2019
DOI: 10.1002/1878-0261.12569
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA‐seq reveals the invasive trajectory and molecular cascades underlying glioblastoma progression

Abstract: Glioblastoma (GBM) is the most common and aggressive primary brain tumor, in which GBM stem cells (GSCs) were identified to contribute to aggressive phenotypes and poor prognosis. Yet, how GSCs progress to invasive cells remains largely unexplored. Here, we revealed the cell subpopulations with distinct functional status and the existence of cells with high invasive potential within heterogeneous primary GBM tumors. We reconstructed a branched trajectory by pseudotemporal ordering of single tumor cells, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…For negatively correlated lncRNAs, ENSG00000254528 ( RP11-728F11.4 ) and ENSG00000267062 ( CTD-2659N19.10 ) ranked among the top four and ten, both of which showed significantly higher expression levels in GBM cells and nearly no expression in normal cells. Notably, VIM-AS1 and WWTR1-AS1 were the top two lncRNAs with the highest correlations between their expression levels and pseudotime along the “stem-to-invasion path” in our previous work ( Pang et al, 2019 ). These findings promoted us to explore the dynamic changes of GBM invasion-associated lncRNAs along the “stem-to-invasion path.” We found that the expression levels of many lncRNAs such as ENSG00000258232 ( RP11-161H23.5 ), ENSG00000267607 ( CTD-2369P2.8 ), and ENSG00000238258 ( RP11-342D11.2 ), gradually increased as cells transferred from cancer stem cell-like state to invasive state ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…For negatively correlated lncRNAs, ENSG00000254528 ( RP11-728F11.4 ) and ENSG00000267062 ( CTD-2659N19.10 ) ranked among the top four and ten, both of which showed significantly higher expression levels in GBM cells and nearly no expression in normal cells. Notably, VIM-AS1 and WWTR1-AS1 were the top two lncRNAs with the highest correlations between their expression levels and pseudotime along the “stem-to-invasion path” in our previous work ( Pang et al, 2019 ). These findings promoted us to explore the dynamic changes of GBM invasion-associated lncRNAs along the “stem-to-invasion path.” We found that the expression levels of many lncRNAs such as ENSG00000258232 ( RP11-161H23.5 ), ENSG00000267607 ( CTD-2369P2.8 ), and ENSG00000238258 ( RP11-342D11.2 ), gradually increased as cells transferred from cancer stem cell-like state to invasive state ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 71%
“…To validate the above observations, we combined the results from our previous work ( Pang et al, 2019 ), in which we identified 12 cell clusters using the same data set. And cluster 3, 4, 7, and 9 showed relatively higher expression of EMT-associated genes.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…They used scRNA-seq based on SMART-seq to analyze a novel parameter they describe as "pseudotime", which refers to transcriptional changes in cells during GBM progression. They were able to describe the path along which GBM stem cells (GSCs) gradually transform into invasive cells, called the "stem-to-invasion path" [172]. The path contains transcription factors and lncRNAs supporting one more time their importance in cancer development.…”
Section: Lncrnas In Tumorsmentioning
confidence: 99%
“…It is paving the future of precision oncology. [150]). A droplet-based scRNA-Seq of patient-derived GBM cells, generated two or three distinct clusters by t-SNE and the Louvain community structure detection algorithm.…”
Section: Machine Learningmentioning
confidence: 99%